The cost of benefits, financial conditions, and employment dynamics in recent U.S. Recoveries - Grace Weishi Gu (University of California, Economics Department, 2013)
This paper explores how much firm-paid employee benefits and firms' financial conditions have contributed to delayed employment recoveries relative to output since 1990, using a DSGE model. Empirically, I document the underexplored pro-cyclicality of per worker benefit costs. Post-1990 period differs from before in that: (1) there have been larger increases of such quasi-fixed employment costs at recoveries; (2) tight financial conditions have also persisted longer into recent recoveries. The model generates 3-to-7-quarter delays in employment recoveries for the post-1990 period but no delay for before, consistent with data; and it produces more than 76 percent of employment volatility.
Keywords: E32; J33; J21; C68; C61; 330; Employment recoveries; benefit costs; extensive and intensive margins; financial conditions; enforcement constraint; DSGE model; business cycle; dynamic programming